2008
DOI: 10.1371/journal.pcbi.1000228
|View full text |Cite
|
Sign up to set email alerts
|

Order-Based Representation in Random Networks of Cortical Neurons

Abstract: The wide range of time scales involved in neural excitability and synaptic transmission might lead to ongoing change in the temporal structure of responses to recurring stimulus presentations on a trial-to-trial basis. This is probably the most severe biophysical constraint on putative time-based primitives of stimulus representation in neuronal networks. Here we show that in spontaneously developing large-scale random networks of cortical neurons in vitro the order in which neurons are recruited following eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 49 publications
11
91
0
4
Order By: Relevance
“…Of the two time-based schemes, rank-order (which is a further reduction of the time-to-first-spike scheme) captures practically all the information carried by the time-to-first-spike scheme. This is consistent with recently published results (Shahaf et al, 2008). A table of all the results used for construction of Figure 3a is presented in supplemental Item 2 (available at www.…”
Section: Representation Of Stimulus Identitysupporting
confidence: 91%
See 2 more Smart Citations
“…Of the two time-based schemes, rank-order (which is a further reduction of the time-to-first-spike scheme) captures practically all the information carried by the time-to-first-spike scheme. This is consistent with recently published results (Shahaf et al, 2008). A table of all the results used for construction of Figure 3a is presented in supplemental Item 2 (available at www.…”
Section: Representation Of Stimulus Identitysupporting
confidence: 91%
“…In this study, using generic networks of cortical neurons as a model system, we follow the path of a stimulus-reconstruction approach to compare the representational efficacy of four types of popular schemes, two rate-base and two time-based: population-counthistogram (Schwartz, 1993;Hupé et al, 2001;Fiorillo et al, 2003), spike-count (Arabzadeh et al, 2006;Foffani et al, 2009;Jacobs et al, 2009), time-to-first-spike (Petersen et al, 2001;Foffani et al, 2004;Johasson and Birznieks, 2004;Gollisch and Meister, 2008;Gollisch and Meister, 2008), and rank-order Van Rullen and Thorpe, 2001;VanRullen et al, 2005;Shahaf et al, 2008). Notwithstanding limitations associated with the stimulus-reconstruction approach in relation to brain function, it served us well in the present context as a mean for estimating the total information content, embedded in a given response feature, about an input.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that stimulus responses stabilized, probably means that subsequent presentation of the cue reactivated the trace and did not interfere with the established activity-connectivity equilibrium. Marom and coworkers showed that repeated stimulation of cultured cortical networks induced site-specific responses that enabled deduction of the stimulation site during up to 24 h (Shahaf et al 2008;Kermany et al 2010). This further supports the view that presentation of the original cue reactivates the trace.…”
Section: Discussionmentioning
confidence: 69%
“…Low-frequency stimulation of neuronal cultures is known to evoke network bursts whose patterns depend on the location of the stimulating electrode [5,6]. The induced reverberating bursts play a key role in changing functional connectivity of neural networks [7][8][9][10][11].…”
mentioning
confidence: 99%